Research at the Faculty of Education Analysis in the context of university accreditation - Tarazona Pérez, Filomeno (2020)
We report the state of the question in research in a stratified sample of 242 students of the VI, VIII and X semester of the Faculty of Education, National University of the Center of Peru, generalizable to a population of 687, on the dimensions of the profile of the research formative and end of the career, research experience, management of intellectual property, responsible behavior and the perception of the development of pedagogical research, contextualized in the standards of University Accreditation; Likewise, 32 teachers who teach research or are directly involved in the function have been surveyed.